Blackdom, New Mexico the significance of the Afro-Frontier, 1900-1930 - Nelson, Timothy E.; Ruffin, Herbert G., 1969- (Lubbock, Texas Texas Tech University Press, 2023)
"A multifaceted look at the freedman township of Blackdom, New Mexico that repositions the community on the history of the American frontier"--
Includes bibliographical references and index.
113627
Keywords: Frontier and pioneer life -- New Mexico -- Blackdom -- African Americans; African Americans -- New Mexico -- History; Blackdom (N.M.) -- History; History